Misoprostol Vs Mifepristone and Misoprostol in Second Trimester Termination of Pregnancy - Nagaria, Tripti (Springer-Verlag, 2012)
OBJECTIVE: The present study was conducted with the aim to assess and comparatively evaluate the safety and efficacy of misoprostol alone and mifepristone with misoprostol for second trimester termination of pregnancy. METHODS AND MATERIALS: The study was conducted on 200 selected cases, divided in two groups of 100 cases each. In the study group mifepristone was given 200 mg 12 h before intravaginal insertion of 600 μg of misoprostol followed by 400 μg every 3 h up to a maximum of 5 doses or until the abortion occurs, whichever occurs early. In the control group only misoprostol was inserted in the same dose regime. The results were analyzed. RESULTS: The success rate in both regimens was 100%. Mean induction abortion interval from the insertion of the first misoprostol tablet was significantly shorter in the mifepristone pretreated group 6.72 ± 2.26 h as compared to 12.93 ± 3.4 h in the misoprostol alone group (P < 0.001). The mean blood loss was slightly higher in the control group. The mean dose of the misoprostol required was significantly less in the study group 1,186 ± 291.64 μg as against 1,736 ± 320.20 μg (P < 0.001). The side effects observed in both the groups were similar mainly nausea vomiting, fever, abdominal cramps. CONCLUSION: Pretreatment with mifepristone 12 h before intravaginal misoprostol significantly improves the induction abortion interval.